Routledge International Handbook of Ignorance Studies - Gross, Matthias; McGoey, Linsey (Taylor & Francis, 2015)
Once treated as the absence of knowledge, ignorance today has become a highly influential topic in its own right, commanding growing attention across the natural and social sciences where a wide range of scholars have begun to explore the social life and political issues involved in the distribution and strategic use of not knowing. The field is growing fast and this handbook reflects this interdisciplinary field of study by drawing contributions from economics, sociology, history, philosophy, cultural studies, anthropology, feminist studies, and related fields in order to serve as a seminal guide to the political, legal and social uses of ignorance in social and political life.